Intertemporal Price Discrimination and Sticky Prices - Phlips, Louis (Quarterly Journal of Economics, 1980)
It is shown that potential entry leads to a marginal-revenue-below-marginal-cost rule, while the possibility of building up inventories (voluntarily!) leads to the intertemporal price discrimination rule, which provides a formal rationalization for normal costing. Equilibrium conditions for a group of firms are derived, using the intertemporal discrimination rule. These conditions can be written as linear estimating equations, with regression coefficients explicitly linked with parameters representing market structure. They imply that, in more concentrated industries, cost increases are less fully transmitted and changes in demand are more fully transmitted into prices than in less concentrated industries.